Factors affecting organization commitment and turnover intention of information technology employees in HCM City - Truong, Ngoc Ha (Journal of Technical Education Science, 2016)
This study used quantitative research methods to identify factors affecting the organizational commitment and turnover intention of Information Technology (IT) employees in the area of Ho Chi Minh City. Data was collected from questionnaires sent directly and through email to employees of companies operation in the IT field. From the theoretical basis, the author has proposed initial research model including six independent variables (job demands, supervisory support, colleagues support, opportunities career promotion welfare and development prospects), an intermediate variable (organizational commitment); and the dependent variable (turnover intention). After testing, the model was adjusted to include the variables: job characteristics, the support of his superiors, the support of colleagues, training opportunities for promotion, organization commitment and turnover intention. Results showed that factors of job characteristics, the support of his superiors, the support of colleagues, training opportunities for promotion were hypothesized to have a positive effect on organizational commitment and organizational commitment have a negative effect on turnover intention.